Femur Fracture in a Jaguarundi (Herpailurus yagouaroundi) - Anesthesia Protocol for Orthopedic Procedure - Vaccarin, Charline; Giovanini da Silva, Janine; Rech Cassanego, Guilherme; De Nardin Peixoto, Gabriella; Dutra Corrêa, Luis Felipe; Coelho Freitas, Gabrielle; Perez Floriano, Beatriz; Vasconcelos Soares, André (Acta Scientiae Veterinariae, 2024)
Background: Performing surgeries and anesthesia on wild animals continues to be a challenge for veterinarians. There is great variability in species and, consequently, in physiological, pharmacological and management peculiarities, which makes it almost impossible to know everything about all existing species. Current literature on anesthetic procedures in felids is scarce and does not address many species of Brazilian fauna. The Herpailurus yagouaroundi, also known as the eyra cat or jaguarundi, is a small feline classified in the puma lineage that inhabits Brazilian territory. The objective of this study was to report the case of a jaguarundi cat with a femur fracture, in order to demonstrate the anesthetic procedure and provide knowledge about wild felines. Case: A jaguarundi (Herpailurus yagouaroundi) of approximately 3 months of age was brought to the University Veterinary Hospital at the Federal University of Santa Maria (UFSM) with a suspected closed fracture of the right pelvic limb. Clinical examination showed prostration, severe dehydration and cachexia, which warranted previous stabilization of the patient prior to anesthesia and surgery. Clinical stabilization consisted of fluid therapy, dietary management and analgesic support for 6 days. At the day of the procedure, premedication was administered intramuscularly with tiletamine and zolazepam for chemical restraint, followed by venous catheterization of the thoracic limb and induction of general anesthesia with intravenous propofol. The trachea was intubated with a Murphy tube of appropriate size and anesthesia was maintained with isoflurane in 100% oxygen. Intraoperative analgesia comprised epidural administration of lidocaine without epinephrine and morphine at the sacrococcygeal space. Monitoring comprised peripheral saturation of oxyhemoglobin, esophageal temperature, heart rate and respiratory rate. Systolic arterial blood pressure was monitored using a vascular Doppler at the thoracic limb. Surgery comprised osteosynthesis of the right femur. Intraoperative complications included hypotension and bradycardia, which were transient and treated with intravenous administration of atropine. At the end of the procedure, the patient was monitored and rewarmed until complete recovery, with cardiorespiratory variables returning to normal values and recovery of consciousness. Finally, the patient was kept in observation at a restricted area to minimize stress caused by the presence of any other animals or people. Discussion: Manipulation of wild animals often requires administration of sedative or anxiolytic drugs to provide safety both for the patient and the team. In felids, an option for chemical restraint is the combination of tiletamine and zolazepam, which provides quick onset sedation with a wide safety margin in healthy patients. The duration of sedation enables most surgical interventions in these species and renders the combination a suitable choice for premedication. Sacrococcygeal epidural using local anesthetic agents and opioids reduces anesthetic requirements in felids and provides desirable analgesia both intra- and postoperatively, thereby minimizing the adverse effects of parenteral analgesics. The hypotension and bradycardia seen during anesthesia were ascribed to intravenous administration of fentanyl. The anesthetic protocol used in this report was considered adequate for surgical repair of a fractured femur in the jaguarundi (Herpailurus yagouaroundi), ensuring satisfactory analgesia with only mild complications and fast uneventful recovery from anesthesia. Due to the lack of reports addressing anesthesia of jaguarundis in current literature, choices of drugs, doses and techniques were based on other felid species, even including the domestic cat. This report can aid veterinary anesthesiologists in formulating an anesthetic protocol for the reported species, which must always take into consideration the clinical scenario and peculiarities of each patient. Keywords: felids, wild cats, zolethyl, rehabilitation, wild medicine. Título: Fratura de fêmur em um gato-mourisco (Herpailurus yagouaroundi) - Protocolo anestésico para procedimento ortopédico Descritores: felídeos, gatos selvagens, zoletil, reabilitação, medicina de selvagens.